Association of the dominant handgrip strength with the hand dimensions of adult Bangladeshi female laborers (Asian Journal of Medical and Biological Research, 2021)
The handgrip strength determines the overall physical health and muscle function of the hand. Nowadays in Bangladesh, female laborers are an important source of work force in many industries. Laborers require more handgrip strength to perform their daily work efficiently. Besides, hand is the part of the body that directly related with handgrip strength, so, the hand dimensions are deemed essential to investigate. Therefore this study is to investigate the association of the dominant handgrip strength with the hand dimensions like hand length, hand breadth, hand span, palm length, palm breadth and wrist breadth of adult Bangladeshi female laborers. Hundred (100) adult female laborers aged between 18 to 45 years, residing in different slums in Dhaka city of Bangladesh were the participants of the present research. Six selected hand dimensions of the right side were measured using the digital slide caliper by direct physical procedure and dominant handgrip strength was measured using a digital handgrip dynamometer. The associations of the dominant handgrip strength with the selected six hand dimensions were tested using Pearson’s correlation coefficient test. The mean value of the dominant handgrip strength of the laborers was 25.6 kg. In present research, the dominant handgrip strength was positively associated with the six selected hand dimensions (hand length, hand breadth, hand span, palm length, palm breadth and wrist breadth). However, the association of dominant handgrip strength with the breadth of hand, palm and wrist reached up to significant level individually. Besides, to get desired success in work of a female laborer, it is important to see the hand anthropometry and handgrip strength, because, better handgrip strength lead to better performance in work.Asian J. Med. Biol. Res. 2021, 7 (3), 230-237